1969
DOI: 10.1039/j39690000101
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of emetine and related compounds. Part X. The synthesis of emetine analogues, including C(3)-bisnoremetine and C(3)-noremetine. Correlation of structure with amoebicidal activity

Abstract: The (&)-ketone (la) (1,3,4,6,7,11 b-hexahydro-9,l O-dimethoxybenzo[a]quinolizin-2-one) has been converted into racemic C(3)-bisnoremetine (IXa) via an N-(3,4-dimethoxyphenethyl) amide which was shown to have the same relative configuration as emetine a t C -l l b and C-2. The (-)-ketone (Ib) [3-methyl derivative of (la)],obtained by asymmetric transformation of the racemic compound, was converted into (-) -C(3)-noremetine (IXb). (-)-1',8a'-Secoemetine (XI) and the (-)-analogues (Xlla-d) have also been prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…2 and 3). These findings confirm the previously studies which have demonstrated that emetine was the most potent amoebicidal agent when compared to its analogues and that changes in structure result in loss of activity (18)(19)(20)(21).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…2 and 3). These findings confirm the previously studies which have demonstrated that emetine was the most potent amoebicidal agent when compared to its analogues and that changes in structure result in loss of activity (18)(19)(20)(21).…”
Section: Resultssupporting
confidence: 92%
“…Three of the structural requirements which are necessary for the activity of emetine (1) are that the C-llb proton has the aconfiguration, the C-i' proton has the a-configuration, and that at the C-2' position there is a secondary nitrogen (7,20). Cross resistance studies using strains of Chinese hamster ovary cells have demonstrated that the phenanthrene alkaloids cryptopleurine (19) and tylocrebine (20) act in virtually an identical manner to emetine at a molecular level (10,17,25). There has been speculation that the two methoxylated aromatic rings of 19 form a planar electronegative area with the nitrogen lone pair 21 which is able to bind to a suitable ribosomal receptor.…”
Section: H3mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the structural requirements for biological potency for mulated by Grollman [15], other considerations involving substitution at the C-3 position in the molecule come into play [6,35]. The (±)-2,3-dehydroemetine derivatives listed in table VIII lacking the appropriate ethyl group at the C-3 position do not have any antileukemic activity and are as inert as (-)-isoemetine in this respect.…”
Section: Discussionmentioning
confidence: 99%